2016
DOI: 10.1007/s40195-016-0408-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, Dielectric and Complex Impedance Properties of xBa0.95Sr0.05TiO3–(1 − x)BiFe0.9Gd0.1O3 Multiferroic Ceramics

Abstract: xBa 0.95 Sr 0.05 TiO 3 -(1 -x)BiFe 0.9 Gd 0.1 O 3 [xBST-(1 -x)BFGO] (x = 0.00, 0.10, 0.20 and 0.25) multiferroic ceramics were prepared by the standard solid-state reaction technique. Structural characterization was performed by X-ray diffraction. All the samples showed rhombohedral distorted perovskite structure. Surface morphology of the ceramics was studied by the field emission scanning electron microscope (FESEM). From the FESEM observation, the grain size was observed to be decreased with increasing BST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…At high frequencies, the values of Z 0 were merged, which conrmed the existence of a space charge zone in our material. 59 A comparable behavior has been observed in the literature. 60,61 For the Ni1200 sample, Z 0 decreased quickly with frequency ( Fig.…”
Section: Ac Conductivitysupporting
confidence: 86%
“…At high frequencies, the values of Z 0 were merged, which conrmed the existence of a space charge zone in our material. 59 A comparable behavior has been observed in the literature. 60,61 For the Ni1200 sample, Z 0 decreased quickly with frequency ( Fig.…”
Section: Ac Conductivitysupporting
confidence: 86%
“…This can be understood by the fact that charge carriers acquired sufficient energy to overcome the potential barrier. 34,35 …”
Section: Resultsmentioning
confidence: 99%
“…This can be understood by the fact that charge carriers acquired sufficient energy to overcome the potential barrier. 34,35 The variation of the imaginary part (Z 00 ) as the function of frequency for different temperatures is shown in Fig. 11.…”
Section: Impedance Analysismentioning
confidence: 99%
“…The values of dc conductivity were calculated by taking the intersection points of semicircles on the Z' axis [M. J. Miah et al (2016)]. From Fig.7-a it was found that the diameter of the semicircle decreasing and the intersection points of the semicircles shifted to lower Z' values with increasing temperature which suggests that the value of grain resistance is decreasing and ζ dc increasing with increasing temperatures.…”
Section: -4-2-1 Complex Impedance Analysismentioning
confidence: 99%